La aplicación de la terapia de aceptación y compromiso (act) en el tratamiento de problemas psicológicos asociados al cáncer - Páez, Marisa Beatriz; Luciano, Carmen; Gutierrez, Olga (Psicooncología, 2005)
The suffering correlated to having cancer is an experience that most patients confront. However, in spite of the psychological impact of such an event, the course of life is affected by the way patients cope with fears, worries, negative memories and thoughts about the future. High believability with such private events occur when a patient behaves according to them and, consequently, his or her life becomes limited and impoverished. Experiential Avoidance Disorder (EAD) is a core component in such cases and it is defined by behavioural rigidity. Acceptance and Commitment Therapy (ACT) is being shown effective in altering the verbal contexts that define EAD and, consequently, in promoting behavioral flexibility. The present paper is aimed only to briefly expose ACT interventions with breast-cancer patients
Keywords: Acceptance and Commitment Therapy; Experiential Avoidance Disorder; Psychological treatment; Breast cancer